Flavor, fragrance and odor analysis - Marsili, Ray , 1946- (CRC Press, 2012)
"Emphasizing SBSE techniques alongside advances in mass spectrometry, sample preparation, gas chromatography (GC)-olfactometry, and electronic-nose technology, this new edition discusses the significant advantage of these methods for flavor and odor studies in the food, cosmetic, and pharmaceutical industries. Written from a practical, problem-solving perspective, it discusses the chemical structures of key flavor and fragrance compounds, contains numerous examples and chromatograms, and emphasizes novel solid-phase micro extraction procedures. It also presents important updates on GC-olfactometry as a tool for studying flavor synergy effects"-- Provided by publisher